A Mechanosensory Receptor TMC Regulates Ovary Development in the Brown Planthopper Nilaparvata lugens - Jia, Ya-Long; Zhang, Yi-Jie; Guo, Di; Li, Chen-Yu; Ma, Jun-Yu; Gao, Cong-Fen; Wu, Shun-Fan (Frontiers in Genetics, 2020)
Transmembrane channel-like (TMC) genes encode a family of evolutionarily conserved membrane proteins. Mutations in the TMC1 and TMC2 cause deafness in human and mouse. However, it is still not well known their functions in insects. Here we cloned three tmc genes, Nltmc3, Nltmc5 and Nltmc7 from brown planthopper. The deduced amino acid sequences share high identity with other species homologues and have the characteristic eight or nine transmembrane domains and TMC domain architecture. These three genes were expressed in all developmental stages and examined tissues. Interestingly, we found Nltmc3 was highly expressed in the female reproductive organ especially in the oviduct. RNAi-mediated silencing of Nltmc3 substantially decreased the egg-laying number and impaired ovary development. These results indicate that Nltmc3 plays an important role in the reproductive behavior of brown planthopper.